Agreement between hip joint center estimation methods and comparisons of dependent hip, thigh, and knee angles - James, C. R.; Atkins, L. T.; Natesan, K.; Likness, A.; Lu, H. C.; Yang, H. S. (Journal of Applied Biomechanics, 2025)
Hip joint center (HJC) location estimation influences dependent angles and clinical interpretations. We examined the agreement between 6 HJC estimation methods; compared hip, thigh, and knee angles; and explored HJC location and thigh angle associations. Pelvis markers were used to estimate HJC location via 6 popular methods using Harrington`s method as the reference standard. HJC limits of agreement analysis and inferential angle comparisons during standing revealed that Bell`s (HJC bias range = 0-11 mm, hip angle difference range = -0.2° to 0.1°) and Vaughan`s (HJC bias range = -5 to 41 mm, hip angle difference range = -0.5° to -5.3°) methods were most and least like Harrington`s but varied by dimension. Stepwise regression showed that anterior-posterior, medial-lateral, and anterior-posterior HJC coordinate differences best explained sagittal (R2 range = .95-.99, P < .001), frontal (R2 range = .83-.99, P < .001), and transverse (R2 range = .54-.72, P < .001) thigh angle differences, respectively. Different HJC methods caused several large sagittal but more minor frontal and transverse plane differences. We urge caution when using different HJC methods.